Oxford Research Encyclopedia of Global Public Health 2020
DOI: 10.1093/acrefore/9780190632366.013.162
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being and Mental Wellness

Abstract: The scientific landscape of wellbeing and mental wellness has developed significantly through interdisciplinary cross-pollination by researchers in molecular genetics, neuroscience, sociology, economics, including traditional and complementary medicine. The public health challenge lies in using this diverse body of scientific evidence to reframe wellbeing and mental wellness within a 21st-century global public health framework that incorporates evidence-based modalities alongside Western biomedical practice. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…However, even in such cases there is a call to recognise the unique developmental stage adolescents are in as they experience significant mental and physical changes. Studies have shown that unlike adults, the adolescent brain is still developing and is more susceptible to changes caused by stress ( Bodeker et al, 2020 ). Additionally, evidence shows that individual factors such as age, sex, and gender present complex interactions with mental wellness among adolescents ( Bodeker et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in such cases there is a call to recognise the unique developmental stage adolescents are in as they experience significant mental and physical changes. Studies have shown that unlike adults, the adolescent brain is still developing and is more susceptible to changes caused by stress ( Bodeker et al, 2020 ). Additionally, evidence shows that individual factors such as age, sex, and gender present complex interactions with mental wellness among adolescents ( Bodeker et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that unlike adults, the adolescent brain is still developing and is more susceptible to changes caused by stress ( Bodeker et al, 2020 ). Additionally, evidence shows that individual factors such as age, sex, and gender present complex interactions with mental wellness among adolescents ( Bodeker et al, 2020 ). Therefore, there is a need to conduct more research with adolescents so that they may participate and contribute to the conceptualisation and operationalisation of mental wellness which suits their needs.…”
Section: Resultsmentioning
confidence: 99%
“…For the scope of this study, professional wellbeing is defined [ 7 , 8 , 9 , 10 ] as an aspect of the professional life comprised of social, psychological, physical and economic wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is briefly described as the capacity to overcome difficulties and adapt successfully under stressful circumstances [ 11 ]. However, as noted by various authors [ 7 , 8 , 9 , 10 ], professional wellbeing is comprised of several domains, including physical wellbeing, economic wellbeing, social wellbeing, and psychological wellbeing. As resilience programmes do not address these all these domains, these programmes are also not very successful.…”
Section: Introductionmentioning
confidence: 99%
“…Happiness has been conceptualized from a biopsycho-social perspective [1,2], and happiness contributes to the overall mental health of an individual [3,4]. By implication, the overall psycho-social wellbeing of an individual to some extent have some connection with happiness [5] such that the more an individual is described as happy the more such individual will experience optimal psycho-social well being which is in turn pointer of optimal mental health [2].…”
Section: Introductionmentioning
confidence: 99%